Rural underemployment and urbanization: Insights from a nine year household panel survey from Malawi - Van Cappellen, Hanne; De Weerdt, Joachim (International Food Policy Research Institute, 2023)
Rural labor markets in Africa are frequently characterized by underemployment, with farmers unable to fully deploy throughout the year one of their most important assets—their labor. Using a nine-year panel data set on 1,407 working-age adults from rural Malawi, we document changes in rural underemployment over this period and how they are associated with urbanization. Nearby urban growth results in increased hours worked in casual labor (ganyu) and in non-agricultural sectors, at the expense of work on the household farm. Improved urban access is also associated with a small increase in wage labor and, at the intensive mar gin, with hours supplied in household enterprises. We draw lessons from these results for policies, investments, and interventions to leverage urban growth for rural development.